Exponential model for simulation data via multiple imputation in the present of partly interval-censored data / Salman Umer and Faiz Elfaki - Umer, Salman; Elfaki, Faiz (2021)
Survival analysis or time-to-event analysis refers to a set of methods to analyze the time between entry to a study and a subsequent event where time to failure of an experimental unit and that could be one of the main types of censored such as Partly Interval-Censored (PIC). In this paper, the likelihoods are applied to estimate the function of survival and parameters in the exponential model when imputation methods such as Multiple Imputation (MI) and Left Imputation (LI) in the present of PIC data. The numerical evidence via simulated breast cancer data suggests that the estimates from MI are more accurate than the LI in the present of PIC data. In additional to that the patient who received chemotherapy and hormone treatment has greater survival rate than a patient who did not receive both treatments.